Kinetics of Zinc Evaporation from Aluminium Alloys Melted Using VIM and ISM Technologies - Albert Smalcerz (MDPI AG, 2021)
Using a vacuum during the smelting and refining of alloys removes dissolved gasses, as well as impurities with high vapour pressure. When smelting is carried out in vacuum induction furnaces, the intensification of the discussed processes is achieved by intensive mixing of the bath, as well as an enhanced mass exchange surface (liquid metal surface) due to the formation of a meniscus. This is due to the electromagnetic field applied to the liquid metal. This study reports the removal of zinc from the Al-Zn alloy containing 6.3 wt.%. Zn. The experiments were carried out with the use of two types of metallurgical devices: the VIM and ISM furnaces. For the experiments carried out in the crucible induction furnace, reduction in the operating pressure in the furnace from 1000 Pa to 10 Pa, together with the increase in temperature from 953 K to 1103 K, is accompanied by a decrease in zinc content in the alloy from 6 to 96%, compared with the initial value. Simultaneously, the overall mass transfer coefficient kZn increases from 5.15 × 10−6 to −1.49 × 10−4 ms−1. For the experiments carried out in the furnace with a cold crucible (T = 953 K), a reduction in the operating pressure in the furnace from 1000 Pa to 10 Pa resulted in a decrease in zinc content in the alloy from 18 to 80%, compared with the initial value. For comparison, the experiments carried out in the crucible induction furnace at 953 K showed a reduction in zinc content in the alloy from 6 to 50%, which means that more intense zinc evaporation is seen in the furnace with a cold crucible. Comparison of ISM and VIM technologies in the removal efficiency of the Al-Zn alloy indicates a higher removal efficiency using the first technology, which, using the same conditions, achieves 80% of the removal efficiency of the component.